Anti‐diabetic effect of banana peel dietary fibers on type 2 diabetic mellitus mice induced by streptozotocin and high‐sugar and high‐fat diet. Issue 10 (29th June 2022) - Wang, Mengyang; Yang, Fan; Yan, Xiang; Chao, Xinyu; Zhang, Wencheng; Yuan, Chuanxun; Zeng, Qingmei
Abstract: We used a high‐fat diet (HFD) and streptozotocin (STZ) to induce type 2 diabetic mellitus (T2DM) mice and evaluated the effect of banana peel dietary fibers (BP‐DFs) as potential hypoglycemic agents. After 5 weeks of intervention with banana peel dietary fibers (BP‐DFs), food intake was reduced, body weight was increased, blood lipids and glucose were reduced, fasting insulin and GLP‐1 levels were increased, and liver and pancreatic tissue damage was reduced. Banana peel soluble dietary fiber (BP‐SDF) has the most significant effect. The results of fecal microbiota analysis showed that BP‐DFs could ameliorates gut microbiome dysbiosis, and all three types of dietary fibers have obvious effects. The results of fecal short‐chain fatty acids (SCFAs) showed that the content of fecal SCFAs was increased after BP‐DFs dietary intervention, and BP‐SDF had the most obvious effect. RT‐PCR experiment results show that BP‐DFs can up‐regulate the mRNA expression levels of PI3K, AKT, IRS‐1, and FOXO1 in the liver of diabetic mice, which indicates that BD‐DFs may play a role in improving insulin resistance and insulin signal transduction via the IRS/PI3K/AKT pathway, improving insulin resistance and insulin signal transduction. Our research may be extended to BP‐DFs, especially BP‐SDF, as the basis for potential dietary intervention to prevent or treat type 2 diabetic mellitus. This work supports future research studies of the anti‐diabetic properties of BP‐SDF in humans. Practical applications: Diabetes can lead to a variety of complications that have a huge impact on health. Dietary fiber may help in lowering blood sugar. Our experimental results showed that banana peel dietary fibers have the effect of reducing food intake, blood sugar, improving liver and pancreas function, increasing the abundance of intestinal flora, and improving the IRS/PI3K/AKT pathway in T2DM mice. Therefore, this study could provide a theoretical basis for the development of functional foods with banana peel dietary fiber. Abstract : The intervention of type 2 diabetic mice with dietary fiber extracted from banana peels. The results showed that it has the effect of reducing food intake, blood sugar, liver and pancreas damage, increasing the abundance of intestinal flora, and promoting the IRS/PI3K/AKT pathway in mice.